2006
DOI: 10.1111/j.1745-4514.2006.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Qualitative Detection Method for Peanut (Arachis Hypogaea) in Foods Using Polymerase Chain Reaction

Abstract: A qualitative method for detection of peanuts in foods using polymerase chain reaction was developed. A universal primer pair CP 03‐5′/CP 03‐3′ was designed to confirm the validity of the DNAs for PCR. The plant‐specific amplified fragments were detected from 13 kinds of plants using the universal primer pair. In addition, for the specific detection of peanuts with high sensitivity, the primer pair agg 04‐5′/agg 05‐3′ was designed to detect the gene encoding the peanut agglutinin precursor. The primer pair spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
(21 reference statements)
1
48
0
Order By: Relevance
“…Moreover, it is important to highlight that although a level of 10 mg·kg −1 is considered relevant for the detection of potentially hazardous residues of undeclared allergens in foods, the achievement of a 10 times lower detection limit, as it is the case of this work, may be highly helpful since minimal amounts of the target allergen can be critical [9]. In addition, it is also important to note that the detection level of about 1.0 mg/kg peanut is achieved without any amplification step and, even so, is lower than those reported so far with PCR-based approaches, which are in the 2 to 10 mg/kg range [9,[22][23][24]. Furthermore, the developed immunosensor is suitable to allow allergen determination in a simple way without requirements of a high number of sample replicates and the use of a high precision thermocycler.…”
Section: Simultaneous Determination Of Ara H 1 and Ara H 2 In Food Samentioning
confidence: 56%
“…Moreover, it is important to highlight that although a level of 10 mg·kg −1 is considered relevant for the detection of potentially hazardous residues of undeclared allergens in foods, the achievement of a 10 times lower detection limit, as it is the case of this work, may be highly helpful since minimal amounts of the target allergen can be critical [9]. In addition, it is also important to note that the detection level of about 1.0 mg/kg peanut is achieved without any amplification step and, even so, is lower than those reported so far with PCR-based approaches, which are in the 2 to 10 mg/kg range [9,[22][23][24]. Furthermore, the developed immunosensor is suitable to allow allergen determination in a simple way without requirements of a high number of sample replicates and the use of a high precision thermocycler.…”
Section: Simultaneous Determination Of Ara H 1 and Ara H 2 In Food Samentioning
confidence: 56%
“…In conclusion, both assays are sensitive and specific tools for the detection of hidden allergens in processed foods. Watanabe et al, 2006 have reported a conventional PCR method combined with gel electrophoresis. In all those cases PCR was only used as a qualitative method for peanut detection in food (for RT-PCR results Ct values are given, but peanut content was not determined).…”
Section: Food Specimens Pcr Assay (%) Positive Samples Specimens Contmentioning
confidence: 99%
“…In addition, the primer pair CP 03-5 0 /CP 03-3 0 , for universal detection of DNA derived from plants, was used to verify the extracted DNAs. 10) This primer pair generated a 123-bp amplified fragment. The sequences of the designed oligonucleotides in this study are listed in Table 1.…”
mentioning
confidence: 99%
“…9) The genomic DNA was extracted from the commercial food products using an anion exchange-type kit (Genomic-tip 20/G, Qiagen) according to the procedure described previously. 10) The extracted DNA was diluted with an appropriate volume of distilled water (DW) to a final concentration of 20 ng/ml and stored at À20 C until needed. When the concentration of the extracted DNA was less than 20 ng/ml, an undiluted DNA extract was used in subsequent PCR analysis.…”
mentioning
confidence: 99%